DRAM, a p53-induced modulator of autophagy, is critical for apoptosis - Crighton,D; Wilkinson,S; O'Prey,J; Syed,N; Smith,P; Harrison,PR; Gasco,M; Garrone,O; Crook,T; Ryan,KM (Cell, 2006)
Inactivation of cell death is a major step in tumor development, and p53, a tumor suppressor frequently mutated in cancer, is a critical mediator of cell death. While a role for p53 in apoptosis is well established, direct links to other pathways controlling cell death are unknown. Here we describe DRAM (damage-regulated autophagy modulator), a p53 target gene encoding a lysosomal protein that induces macroautophagy, as an effector of p53-mediated death. We show that p53 induces autophagy in a DRAM-dependent manner and, while overexpression of DRAM alone causes minimal cell death, DRAM is essential for p53-mediated apoptosis. Moreover, analysis of DRAM in primary tumors revealed frequent decreased expression often accompanied by retention of wild-type p53. Collectively therefore, these studies not only report a stress-induced regulator of autophagy but also highlight the relationship of DRAM and autophagy to p53 function and damage-induced programmed cell death.